How, Why and When: Nursing Staff's Experiences of Working With Suicide Risk Assessment Instruments - Rikard Wärdig; Isabella Wallerstedt; Anna Mattison Nyström; Sally Hultsjö (Wiley, 2024)
ABSTRACT Aims and objectives To describe psychiatric nursing staff´s experiences of working with suicide risk assessment instruments. Background Around the world, approximately 720,000 people die by suicide each year, of which almost 20% have an ongoing contact with specialist psychiatry during their last month alive. To identify which patients have an increased risk of suicide is a highly important task for nursing staff. Suicidal behaviour is complex and unpredictable. Nursing staff work closely with patients in everyday psychiatric care and often possess unique patient knowledge. These professionals must therefore be able to know when a patient's eventual suicidality requires further attention and efforts. Design A descriptive qualitative study. Methods Convenience sampling including nursing staff with more than 2 years of experience in specialist psychiatry. The data collection took place through semi‐structured interviews and was then analysed according to conventional content analysis. Results The nursing staff felt that a natural conversation is superior suicide risk assessment instruments and that experience and patient knowledge are the primary factors for facilitating a suicide risk assessment. This meant that some nursing staff rarely used suicide risk assessment instruments, although they sometimes could be a useful support in the conversation and provided a sense of personal security when documenting results. Conclusion Suicide risk assessment instrument can be significant and helpful in certain cases, but the essential components of a suicide risk assessment consist of a conversation to understand the meaning of suicide from the patient's perspective. Patient or Public Contribution Psychiatric nursing staff contributed to this study by sharing their experiences through interviews.